New Hamacantha from Peru and resurrection of Zygherpe as subgenus (Demospongiae, Poecilosclerida, Hamacanthidae) - Hajdu, E.; Hooker, Y.; Willenz, P. (Zootaxa, 2015)
Two species of Hamacantha with tylostyles are reported here for the Peruvian coast, namely H. desmacelloides sp.nov. and H. hyaloderma. The former is the first species in the genus with apically microspined sigmas, similar to those known to occur in Neofibularia, and recently reported from genera Biemna, Desmacella, Rhabderemia and Sigmaxinella. Hamacantha hyaloderma was previously known from Mexico to Canada, and is here reported for the first time from the south east Pacific. The finding of a second species with tylostyles led us to reinstate subgenus Hamacantha (Zygherpe). The possible phylogenetic significance of apically microspined sigmas is discussed in view of recent findings on the basis of molecular data.